Post-Buckling Behavior of Variable-Arc-Length Pipe due to Internal Fluid Motion - Nathabumrung, Wichawat; Padthomfang, Panithan; Tima, Tanakorn; Klaycham, Karun (การประชุมวิศวกรรมโยธาแห่งชาติ ครั้งที่ 25, 2020)
This paper presents the large deflection of variable-arc-length pipe transporting fluid under a compressive load. The set of nonlinear governing equations of the pipe is derived by considering the equilibrium of force and moment and the geometric relation of the differential pipe segment in two-dimension. The set of governing equations yields the nonlinear first-order differential equation, which corresponds to the two-points boundary value problem. The numerical solution is solved by using the shooting method. The present numerical result is found to be accurate when compares with the elliptic integral solution provided in the available literature. Three equilibrium states can be found from the load-displacement curve of the pipe including stable, unstable, and critical equilibrium states. The numerical results also indicate that the effect of the pipe weight and the compression load at the end cause to decrease the critical velocity of the transporting fluid.